Long-term Remission of Atopic Dermatitis after Discontinuation of Dupilumab - Shoko Miyamoto; Yasutomo Imai; Masaru Natsuaki; Kiyofumi Yamanishi; Nobuo Kanazawa (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)